PENYULUHAN ANEMIA PADA ANAK DAN REMAJA PUTRI DI JEMAAT GMIT IMANUEL NATOEN SULAMU DESA PANTULAN KEC SULAMU KAB KUPANG - Roslin E.M. Sormin; Maria V. Nuhan; Yosefa Sarlince Atok (Batara Wisnu : Indonesian Journal of Community Services, 2021)
Implementing this Community Service program aims to reduce the morbidity of anemia in children and young women in the village of Sulamu District reflection of Kupang Regency. This activity was held at GMIT Imanuel Natoen Sulamu Bounce Village of Sulamu District of Kupang Regency. The targets and partners of this activity are children and young women in the Congregation of Imanuel Natoen Sulamu, Lecturer and student of STIKes Maranatha Kupang. Implementation of anemia PKM activities amid the COVID-19 pandemic situation through 3 stages: the preparation of facilities and infrastructure, the stage of socialization, and evaluation. As for the results of the implementation of amenia counseling, namely the increase in the knowledge of young women of the Church of Emmanuel Natoen Sulamu after being given counseling.